Description of the epidemiological characteristics of work-related eye injuries in Spain: a retrospective study - Sergio Martin-Prieto; Cristina Álvarez-Peregrina; Israel Thuissard-Vasallo; Carlos Catalina-Romero; Eva Calvo-Bonacho; César Villa-Collar; Miguel Ángel Sánchez-Tena (BMJ Open)
Objective To describe the epidemiological characteristics and trends of work-related eye injuries (WREIs) in Spain over a 10-year period by sex, age and occupational sector.Design and settings A descriptive, retrospective and longitudinal study based on data from workers insured by a labour insurance company in Spain from 2008 to 2018 was presented. The study considered the ratio of the number of WREI per 100 000 population and the relative risk of suffering an ocular injury. WREIs were characterised by sex, age and occupational sector of injured workers.Primary and secondary outcome measures Ratio of the number of WREI.Participants In Spain, all workers are insured by a labour insurance company that provides cover in the event of work-related accidents. In this study, we have included all workers insured by one of these insurance companies, IBERMUTUA, with workers in all areas of Spain.Results The study included 50 265 WREI in the company over the 10-year period. Most of the injuries occurred in males (44 445; 88.4%), in 35–44 age group (15 992; 31.8%) and in industry workers (18 899; 42.6%). The average incidence was 429.75 per 100 000 workers insured and 4273.36 per 100 000 IBERMUTUA accidents (related and not related to eyes). Males, 16–24 age group and industry occupational sector group, have the highest incidence for WREI. The incidence of WREI decrease over the study period in all variables. Males have 6.56 (95% CI 6.38 to 6.75) times more risk of suffering WREI than females. 16–24 age group have 1.77 (95% CI 1.71 to 1.83) times more risk than in the group of workers older than 55. Finally, industry workers have 7.73 (95% CI 7.55 to 7.92) times more risk than services workers.Conclusions The risks of suffering WREI is higher for males, younger and less experienced workers, and for those who works in a manual task.